Averaging method in some problems of the theory of nonlinear oscillations - Petryshyn, R. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
By using the averaging method, we prove the solvability of multipoint problems for nonlinear oscillation systems. The deviation of the solutions of original and averaged problems is estimated.